SISTEM PENGENDALIAN INTERN DALAM PENCEGAHAN FRAUD PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) PADA KABUPATEN BANGKALAN - Chairun Nisak; - Prasetyono; Fitri Ahmad Kurniawan (JAFFA, 2013)
The purpose of this research is to analyze the implementation of internal control system toward fraud prevention in local government Institution (Satuan Kerja Perangkat Daerah/SKPD). The data of this research were collected by using questionnaires to the chairman of local government Institution (SKPD). The sampling method used simple random sampling. The data had been analyzed to test the hypothesis using the Multiple Regression Analysis. The result of this research showed that the control environment, risk assessment, control activities, information and communication, and monitoring activities had significant influence to the prevention of fraud both simultaneously and partially.